The study of glycolic acid ethoylate 4-nonylphenyl ether on drug reduction - Soali, Emma; Hayder, Abdul Bari; Hasan, Zulkafli; Rahman, Md. Mokhlesur (Asian Network for Scientific Information, 2010)
Power saving is the major reason to study the problem of drag in transporting system. The performance of glycolic acid ethoxylate 4-nonylphenyl ether as drag reducing anionic surfactant was studied experimentally in closed loop circulation system at room temperature. The major investigated variables is operation flow rate which from 11235 to 78645 Re and the solution concentration (ppm), which 200, 300, 400, 500 and 600, respectively. The selected ratio of testing pipe length to diameter (L/D) is equal to 59. The specific conductivity test was conducted to find the CMC of anionic surfactant. It was found that the CMC occurred within the range of 100 to 200 ppm of solution. The maximum drag reduction can be achieved up to 14%. The critical Re was found at 33705 to 56175. The alignment of micelle with the eddies in turbulent flow was identified as the source of drag reduction in pipes.